1996
DOI: 10.1161/01.cir.93.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Antagonist TCV-116 Reduces Graft Coronary Artery Disease and Preserves Graft Status in a Murine Model

Abstract: These findings show that AT1-R blockade is at least as effective as ACE inhibition in management of chronic allograft rejection and suggest that Ang II may play an important role in chronic allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…A recruitment of T cells in TI of the kidney, as documented by CD 4 and CD 8 staining, could be observed in Ang II-infused rats. When infused rats were treated with high-dose olmesartan, T-cell infiltration was absent.…”
Section: Ti Injury In Ang Ii-infused Ratsmentioning
confidence: 75%
“…A recruitment of T cells in TI of the kidney, as documented by CD 4 and CD 8 staining, could be observed in Ang II-infused rats. When infused rats were treated with high-dose olmesartan, T-cell infiltration was absent.…”
Section: Ti Injury In Ang Ii-infused Ratsmentioning
confidence: 75%
“…In contrast, other strategies have sought to directly inhibit VSMC proliferation, a late component of transplant arteriosclerosis (5,48). It has been shown that receptor antagonists for VSMC mitogens (49,50) and rapamycin (51-53), a potent VSMC growth inhibitor, are effective at inhibiting chronic graft vasculopathy in animal models. Molecular strategies that target VSMC growth have also been examined in models of chronic graft vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, NF B decoy markedly attenuated myocardial cell infiltration, the score was statistically less than those of the other groups. Immunohistochemically, [14][15][16] native hearts and isografts showed no enhancement of ICAM-1, VCAM-1, MHC class I, MHC class II or NF B expression. These were enhanced in nontreated or scrambled ODN transfected allografts of minor mismatch group at day 28, mainly observed in myocardial interstitium with mononuclear cell infiltration.…”
Section: Graft Survivalmentioning
confidence: 99%
“…Sections were incubated with primary antibodies against murine intercellular adhesion molecule (ICAM)-1 (YN1/1.7), vascular cell adhesion molecule (VCAM)-1 (MK/2) (provided by Prof Ko Okumura, Juntendo University, Japan), MHC class I and class II (Funakoshi, Tokyo, Japan) and NF B (Santa Cruz Biotechnology, Santa Cruz, CA, USA) for 12 h at 4°C. [14][15][16] Antibody-biotin conjugate was detected with Vectastain ABC Kit (Vector, Burlingame, CA, USA) used according to the manufacturer's instructions. Enzyme activity was detected with diaminobenzidine (0.5 mg/ml) with 0.05% NiCl in 50 mm Tris buffer, pH 7.5.…”
Section: Immunohistochemistrymentioning
confidence: 99%